Influência do certifica minas café nas lavourasa cafeeiras de alfenas, sul de minas gerais - Do Amaral, Ana Maria Santana; Da Silva, Adriano Bortolotti; Angelocci, Marina Ariente; Putti, Fernando Ferrari [UNESP]; De Almeida Coelho, Thamiris Lentz; Campos Corsini, Wanessa Tavares; Dos Santos Corsini, Fábio; Miranda, José Messias (My University, 2017)
The Brazilian coffee production is outstanding in the world, especially the specialty coffee produced in Minas Gerais. The domestic and especially the international market are increasingly demanding the consumption of agricultural products; so coffee certification becomes a form of quality assurance and sustainable production. This study aimed at verifying whether the Certifica Minas Café coffee certification is a valid management tool for producers and the gains obtained from the quality of certified coffee. A semi-structured questionnaire was used to carry out a research among coffee producers of the Alfenas regional office served by the office of EMATER-MG in Machado-MG. The analysis revealed that certification stimulates the producer to better manage his or her property, helps to increase the production of specialty coffee and increases profitability. Therefore it is a valid management tool for small and medium producers, once large producers usually have an operational management control in their properties. However it is important that EMATER-MG be aware that the more the certified producers share their experience in the certification process with uncertified farmers, the greater the number of producers interested to join the certification program, once person-to-person advertising is still a market strength.
Certifica minas café certification in coffee plantations in the Alfenas region - south of Minas Gerais
Keywords: Certification; Coffee; Management tool; Quality